Interaction between ganglioside GM1 and diosgenin in langmuir monolayers at the air/water interface. Issue 2 (1st April 2013) - Hao, Changchun; Zhang, Lei; Sun, Runguang; Yang, Jing; He, Guangxiao
Summary The interaction between ganglioside GM1 (GM1) and diosgenin (Dios) in mixed monolayers was investigated using surface pressure measurements and atomic force microscopy (AFM). The miscibility and stability of the mixed monolayer was evaluated both in a qualitative and quantitative way in terms of the excess mean molecular area (ΔAex), excess Gibbs energy (ΔGex). The ΔAex of mixed GM1/Dios monolayer was found to have positive deviations from ideality at low Dios mole fractions (XDios = 0.2). Above XDios = 0.2, there was a marked negative deviation from ideal mixing, indicating attractive interaction between GM1 and Dios. According to the values of excess Gibbs energy of mixing monolayers, the more stable monolayers assayed was: XDios = 0.6. The compressibility coefficient was assessed at various surface pressures. The monolayer of Dios was more elasticity or rigid than GM1. The AFM images for the mixed monolayers at 30 mN/m indicated there was obvious phase separation in the mixed monolayers. These findings will provide useful information for understanding the interaction between drug and lipids. SCANNING 36:218–223, 2014. © 2013 Wiley Periodicals, Inc.